The environmental challenge for central European economies in transition / edited by Jürg Klarer and Bedřich Moldan. - Klarer, Jürg.; Moldan, Bedřich. (Wiley, 1997)
An analysis of the nature and scope of the environmental challenge in the main countries of Central and Eastern Europe, including Albania, Bulgaria, Hungary, Poland, the Czech Republic and Slovakia.